THE INFLUENCE OF SOCIAL CAPITAL, HUMAN CAPITAL, AND NATURAL CAPITAL ON ECONOMIC GROWTH AND COMMUNITY WELFARE - M Amin (Edukasi Islami : Jurnal Pendidikan Islam, 2020)
Research conducted in West Nusa Tenggara using the Solow Development Theory, to link the variables of social capital, human capital, and natural capital to economic development and people's welfare, it was found that social capital had a significant effect on economic development and people's welfare. Then the research results can provide an answer about the phenomenon of the level of people's welfare in West Nusa Tenggara Province, which is currently still below the national average. Based on the research results, it can be denied that to improve the welfare of the people in West Nusa Tenggara, a social capital-based economic growth management policy is needed. Then these actions must be taken because economic growth is a good intervention variable for social capital. Also, it is necessary to consider the regional government so that the management of the financial area is based on economic growth which is necessary for the welfare of the people in West Nusa Tenggara.